Determinants of cryptococcal antigen (CrAg) screening uptake in Kampala, Uganda: An assessment of health center characteristics. (1st April 2022) - Srishyla, Diksha; Saemisch, Gabriel; Turya, Fred; Nalintya, Elizabeth; Jjunju, Samuel; Kagimu, Enock; Rutakingirwa, Morris K; Skipper, Caleb P; Boulware, David R; Meya, David B; Rajasingham, Radha
Abstract: Cryptococcal antigen (CrAg) screening and pre-emptive antifungal therapy for people with CD4 cell counts <100 cells/μl are recommended by the World Health Organization and several national HIV guidelines. We sought to evaluate CrAg screening program implementation across Uganda, in relation to health center level and distance from the capital. We conducted a cross-sectional study of 22 health centers across southern Uganda from April to June 2019. We reviewed laboratory records regarding number of CD4 cell count tests performed, proportion of outpatients with CD4 counts <200 cells/μl, and number of CrAg screening tests performed. We administered surveys to health center staff to understand barriers to advanced HIV care. We observed no significant difference in health center level and performance of CrAg screening; with each subsequent health center level, there was 1.17-fold (95% CI: 0.92–1.41) higher odds of CrAg screening performed per level. CrAg screening uptake was not associated with distance from the capital city (odds ratio = 0.96, 95% CI: 0.89–1.04). Qualitative data from surveys indicated that limitations to uptake of CrAg screening were secondary to dysfunctional CD4 machines, lack of provider awareness of CrAg screening guidelines, and inadequate/intermittent supply of CrAg tests. There were no significant associations between CrAg screening uptake and level of health center or distance of health center from the capital city. We identified systemic barriers to CrAg screening related to inadequate CD4 testing, insufficient knowledge regarding national screening guidelines, and irregular laboratory testing supplies. Lay summary: The objective of this study was to evaluate cryptococcal antigen (CrAg) screening program implementation in Uganda, by type of healthcare center and by distance from the capital city. CrAg screening uptake was not associated with distance from the capital city, or the type of healthcare center.